PHILOSOPHY OF DIGITAL CONSCIOUSNESS: NEW HORIZONS FOR UNDERSTANDING CONSCIOUSNESS IN THE AGE OF TECHNOLOGY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the study of the transformation of ideas about consciousness in the context of the rapid development of digital technologies and artificial intelligence (AI). The author considers the possibility of the existence of consciousness not only in biological systems, but also in artificial ones, which opens up new horizons for philosophical and scientific understand-ing of its nature, criteria and boundaries. The work analyzes the key challenges associated with the modeling of consciousness, the ethical aspects of development and human interaction with technology. The article emphasizes the importance of the philosophy of digital consciousness as a tool for understanding technological changes and shaping the future, in which technologies contribute to the progress of humanity, preserving its uniqueness and identity.
Keywords: digital consciousness, artificial intelligence, philosophy of technology, transformation of consciousness.